“Holiday heart” syndrome in rats: Features of microcirculation, functional state and anatomy of the heart - S. A. Kryzhanovskii; I. B. Tsorin; E. O. Ionova; M. B. Vititnova; S. A. Simonenko; L. G. Kolik (Фармакокинетика и Фармакодинамика)
Purpose of the study. Studying the features of microcirculation, functional state and anatomy of the heart using the “Holiday Heart” syndrome model in rats we developed.Materials and methods. Experiments were carried out on white outbred male rats. The “Holiday Heart” syndrome was modeled as follows: animals received a 10 % aqueous ethanol solution as the only source of fluid for the first 10 days, then tap water for 10 days, and again a 10 % aqueous ethanol solution for the next 10 days. One day after the end of the repeated intake of alcohol, the animals were taken into the experiment. Animals that received free access to tap water served as control. Some rats in the experimental group (n = 10) had an echocardiogram recorded before the start of the experiment, and on the 31st day of the experiment, after which the level of microcirculation of blood and lymph in the brain and heart was measured using laser Doppler flowmetry. In the remaining animals (n = 10), microcirculation of blood and lymph in the brain and heart was assessed on the 3rd day of alcohol deprivation.Results. Analysis of the obtained data showed that in the conditions of the “Holiday Heart” syndrome model, significant changes occur in the anatomy, functional activity and geometry of the heart: there is a significant thinning of the anterior wall of the left ventricle heart (LV), an increase in systolic and diastolic volumes and sizes of the LV and a significant (p = 0.0018) decrease in its inotropic function. These changes occur against the background of a significant (p = 0.0081) decrease in the level of blood microcirculation in the myocardium, however, on the 3rd day of deprivation, blood flow in the microvessels of the heart increases statistically significantly (p = 0.0285).Conclusion. In model experiments reproducing the “Holiday Heart” syndrome, it was shown for the first time that ethanol causes significant changes in the microcirculation, anatomy, functional activity and geometry of the left ventricle of the heart, which, apparently, can play a key role in the formation of myocardial electrical instability pathognomonic for this syndrome.